2019
DOI: 10.5539/ijel.v9n6p77
|View full text |Cite
|
Sign up to set email alerts
|

Is Listening Comprehension a Comprehensible Input for L2 Vocabulary Acquisition?

Abstract: Vocabulary learning has received considerable attention from reading comprehension input in second language acquisition research. However, a little is known about vocabulary gains from listening comprehension input. This paper aims to review L2 vocabulary gains from listening comprehension input in comparison to reading comprehension and reading while listening comprehension activities. We search for the terms “vocabulary learning”, “vocabulary acquisition”, and &ldq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Rodrigo (2004) concluded that vocabulary and grammar can be acquire better through comprehensible input and the hypothesis of comprehensible input-based approaches are more effective than traditional methodology. Secondly, as for comprehensible input device, the study's investigation complements the findings of Pigada and Schmitt (2006) and Mushait and Mohsen (2019), who totally affirmed that reading and listening are two major means of comprehensible input providing. Comparably, the participated teachers responded to the open-ended question that they mostly used some activities such as videos, songs, storytelling and specialized reading texts.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Rodrigo (2004) concluded that vocabulary and grammar can be acquire better through comprehensible input and the hypothesis of comprehensible input-based approaches are more effective than traditional methodology. Secondly, as for comprehensible input device, the study's investigation complements the findings of Pigada and Schmitt (2006) and Mushait and Mohsen (2019), who totally affirmed that reading and listening are two major means of comprehensible input providing. Comparably, the participated teachers responded to the open-ended question that they mostly used some activities such as videos, songs, storytelling and specialized reading texts.…”
Section: Discussionsupporting
confidence: 75%
“…Regarding vocabulary acquisition, Mushait and Mohsen (2019) shared the idea that vocabulary acquisition is mostly based on listening and reading comprehensible input. Reading and listening are considered vital devices in providing meaningful input to language learners.…”
Section: Vocabulary Acquisition From Reading and Listeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the widespread belief that language knowledge is linked to the ability to produce it through speaking and writing (Nunan, 2002), it is well established that listening and reading abilities allow L2 learners to obtain comprehensible input (Krashen, 1985). Mushait and Mohsen (2019) point out that second language acquisition theory seeks adequate inputs to acquire a foreign language by providing a "comprehensible input" beyond the students' proficiency level. They further argue that, previously, input was restricted to text material presented in printed or audio forms through a single input, i.e., reading or listening contexts.…”
Section: Listening and Reading Comprehensionmentioning
confidence: 93%